Adoption of the International Financial Reporting Standard IFRS11 Constraints and Remedies (Application in Basra Gas Company) - Saeed, Rasha Abid almajed; abidulaa ibraheem, mohammed (Journal of Economics and Administrative Sciences, 2020)
The aim of this study is to highlight on the concept of joint arrangements and projects in accordance with IFRS 11, in addition, the study also focuses on accounting standards and IFRSs which are relevant to this standard.  With a description of the legislative and accounting challenges in the Iraqi environment facing the application of IFRS 11, as well as studying the reality of accounting in such economic activity of companies operating in this sector.In order to achieve the study objectives, the researcher conducted a comparative analysis between IFRS 11 (Joint Arrangements) and the Iraqi Unified Accounting System, In the second step, IFRS 11 is applied to the Basrah Gas Company's (research sample).The study found some conclusions one of the important is a wide gap between the unified accounting system which is applied in Iraq and the IASs/ IFRS, and with local accounting application requirements, namely, the lack of disclosure in the financial reports of joint arrangements, obstacles and challenges in the local environment from the legal and accounting aspects when adopting or applying the IFRS11.The study also presented a set of recommendations, the most important of which is the trend towards adopting the financial reporting standard (IFRS 11) by the Iraqi companies through entering into partnerships that contribute to strengthening the national economy in order to increase expertise and access to technology and create job opportunities to alleviate unemployment.